Forensic investigation of explosions - Beveridge, Alexander (International forensic science and investigation series, 2012)
Now in its second edition, Forensic Investigation of Explosions draws on the editor's 30 years of explosives casework experience, including his work on task forces set up to investigate major explosives incidents. Dr. Alexander Beveridge provides a broad, multidisciplinary approach, assembling the contributions of internationally recognized experts who present the definitive reference work on the subject.Topics discussed include:The physics and chemistry of explosives and explosionsThe detection of hidden explosivesThe effect of explosions on structures and personsAircraft sabotage investigationsExplosion scene investigationsCasework managementThe role of forensic scientistsAnalysis of explosives and their residuesForensic pathology as it relates to explosivesPresentation of expert testimonyWith nearly 40 percent more material, this new edition contains revised chapters and several new topics, including:A profile of casework management in the UK Forensic Explosives Laboratory, one of the world's top labs, with a discussion of their management system, training procedures, and practical approaches to problem solvingProperties and analysis of improvised explosivesAn examination of the Bali bombings and the use of mobile analytical techniques and mobile laboratoriesThe collection, analysis, and presentation of evidence in vehicle-borne improvised explosive device cases, as evidenced in attacks on US overseas targetsThis volume offers valuable information to all members of prevention and post-blast teams. Each chapter was written by an expert or experts in a specific field and provides well-referenced information underlying best practices that can be used in the field, laboratory, conference room, classroom, or courtroom.